Stakeholder Motivation in Local Collaboration: A Study of Education in Deli Serdang Regency - Anwar Fuad Alamsyah Lubis (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study explores and seeks to understand the motivations behind stakeholder involvement in the implementation of an educational program called CERDAS (Percepatan Rehabilitasi dan Apresiasi Sekolah). Each stakeholder holds different orientations but is confronted with similar challenges. Therefore, it is compelling to critically examine the motivations underlying each stakeholder's behavior. Theoretical framework:   The theoretical framework employed in this research is the relational values theory by Murphy and Stott, which includes instrumental, integrative, intrinsic, and extrinsic values. These relational values serve to explain the motivations of the stakeholders involved. Literature review: The literature review is grounded in governance theory, which emphasizes the necessity of joint governance. This perspective is particularly relevant in examining stakeholder motivations within collaborative efforts. Methods: This study uses a qualitative approach with datacollection techniques in the  form  of  observation,  in-depth  interviews,  and  documentation. Results: The findings reveal that collaboration can be sustained when stakeholders’ relational values are aligned and configured toward a shared goal. Each stakeholder brings distinct relational values to the collaboration. Implications: This study suggest that the success and sustainability of local collaboration in education is highly dependent on the alignment of relational values ​​between stakeholders with different motivations. Novelty: The novelty of this study on local collaboration lies in its focus on uncovering the motivations of all stakeholders involved.